2014
DOI: 10.1074/jbc.m114.570143
|View full text |Cite
|
Sign up to set email alerts
|

A Cleavage-potentiated Fragment of Tear Lacritin Is Bactericidal

Abstract: Background:The wet visual surface of the eye is essentially a sterile environment. Results: Proteolytic processing of the prosecretory mitogen lacritin in tears releases a fragment that is required for much of the bactericidal activity of tears. Conclusion:The protease-released C terminus of lacritin is bactericidal under physiological conditions. Significance: All known lacritin activities are bundled within the same C-terminal region, although at different dose optimum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 64 publications
0
47
0
Order By: Relevance
“…Many other tear proteins, including a-and b-defensins, and cathelicidin have antimicrobial activities against commensals and pathogens; however, only few (eg, lipocalin-derived peptide) are insensitive to the ionic strength of normal tear fluid. [27][28][29] Similarly, other TSP-derived peptides were previously reported to carry an antimicrobial activity against Escherichia -/ -(n = 7) and C57BL/6/(n = 7) mice. To determine the antibody titers, serial dilutions of serum derived from the TSP-1 -/ -and wild-type (WT) mice were exposed to bind to the CNS sp.…”
Section: Discussionmentioning
confidence: 99%
“…Many other tear proteins, including a-and b-defensins, and cathelicidin have antimicrobial activities against commensals and pathogens; however, only few (eg, lipocalin-derived peptide) are insensitive to the ionic strength of normal tear fluid. [27][28][29] Similarly, other TSP-derived peptides were previously reported to carry an antimicrobial activity against Escherichia -/ -(n = 7) and C57BL/6/(n = 7) mice. To determine the antibody titers, serial dilutions of serum derived from the TSP-1 -/ -and wild-type (WT) mice were exposed to bind to the CNS sp.…”
Section: Discussionmentioning
confidence: 99%
“…In silico analysis by the Protease Specificity Prediction Server suggested Lacrt’s serine protease sensitivity liberates the C-terminal amphipathic α-helix intact for downstream co-receptor binding to syndecan-1 (Table 2) [65]. Recent reports suggest that this proteolysis releases an α-helical carboxy terminal peptide from Lacrt that displays bactericidal activity, which may represent an innate defensive immunity on the ocular surface [66]. The cleavage may be regulated by serine proteases, as specific protease inhibitors (chymostatin, leupeptin) or boiling were reported to inhibit proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The carboxy-terminal amphipathic α-helix of Lacrt has been reported to associate with co-receptor syndecan-1, which thus regulates functional specificity [20] and maintains corneal epithelium homeostasis [19]. New data suggested that the same region undergoes proteolytic processing and demonstrates crucial bactericidal activity in tears [66]. Similar to our recent reports in SV40-transduced human corneal epithelial cells (HCE-Ts)[39], Lacrt triggers a cascade of mitogenic events involving Gαi or Gαo–PKCα-PLC–Ca 2+ –calcineurin–NFATC1 and Gαi or Gαo–PKCα-PLC–phospholipase D (PLD)–mTOR pathways [18].…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has shown that the main antimicrobial activity of lacritin relied on N-65, a form of lacritin (lacking 65 amino acids from its N-terminus) with a potent antimicrobial activity (49). Its core antimicrobial activity maps to the last 15 amino acids (N-15), the sequence AQKLLKKFSLLKPWA.…”
Section: Accepted Manuscriptmentioning
confidence: 98%